Pharmacological approaches to antibody‐mediated rejection—Are we getting closer?. Issue 10 (15th August 2020) - Kwun, Jean; Knechtle, Stuart
Abstract : Animal research and initial clinical experience suggest that combined targeting of plasma cells and costimulation blockade effectively reduces the barrier of humoral immunity to organ transplants. See the article from Jain et al on page 2675 .